Multidimensional poverty in Chhattisgarh: a measure for action - Oxford Poverty and Human Development Initiative (Oxford Poverty and Human Development Initiative, 2020)
This briefing provides an overview of multidimensional poverty in the state of Chhattisgarh in India. According to the global Multidimensional Poverty Index (MPI), Chhattisgarh had a dramatic reduction in multidimensional poverty. Ongoing policy investments will continue that remarkable trend.